Displacement and development: Evidence from a graduation program for Somalia’s ultra-poor - Leight, Jessica; Hirvonen, Kalle; Karachiwalla, Naureen; Rakshit, Deboleena (International Food Policy Research Institute, 2025)
While the population of internally displaced people around the world continues to grow, evidence around strategies to sustainably enhance livelihoods among IDPs remains extremely limited. We present findings from a randomized trial of an ultra-poor graduation program targeting IDPs in urban Baidoa, Somalia; the intervention pro-vided cash transfers, an asset transfer or technical training program, and facilitated savings groups. Our findings suggest that two years following program launch, the intervention has led to significant increases in consumption, assets, and savings; however, these effects seem to be driven almost exclusively by increased livestock production. An exploration of heterogeneous effect using generalized random forest methods further suggests that the positive effects of the treatment are dramatically larger for smaller households characterized by lower dependency ratios.